Avaliação de dialetos brasileiros: o sotaque (Revista de Estudos da Linguagem, 1997)
This paper presents scores of attitude tests applied in five Brazilian cities: Belo Horizonte, Rio de Janeiro, Florianópolis, João Pessoa and Porto Alegre. The results made possible the identification of a narrow relationship between self-confidence and cultural identity: the more people in a city are aware of the difference between their dialect and the dialect used by the media the proudes they are of their accent. It is exactly this accent which received the highest scores of acceptability by the speakers of other accents.